Implementasi Qr Code Menggunakan Google Application Programming Interface (API) dalam Membangun Sistem Informasi Warehouse dengan Metode Extreme Programing Berbasis Web (Studi Kasus: PT Bell Flavors & Fragrances Indonesia) - Ardika, Juli Bima; Ratama, Niki (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
PT. Bell Flavors & Fragrances Indonesia, which is a private company in the field of distributors of chemicals and products, namely, Flavors, Fragrances, Botanicals, Ingredient Specialties. The current transaction process at PT. Bell Flavors & Fragrances Indonesia by inputting data into Microsoft Excel which before being input into Microsoft Excel is written manually on HVS paper, it takes quite a lot of time and causes errors in recording and there is no QR Code to view item details. The extreme programming method is used to solve problems that occur with the planning, design, coding, and testing stages. Produce a warehouse information system by implementing a QR Code to view the details of goods made using the PHP programming language, using Unified Modeling Language (UML) object-oriented analysis such as Use Case diagrams, Sequence diagrams, Activity diagrams and Class diagrams and tested using Black Box testing, testing White Box and questionnaire testing.